The beekeper next door - Thorne, Danielle (Love inspired., 2024)
"Returning to his hometown to clean up his late parents' home, professor Heath Underwood has no intention of making his stay permanent. Especially when he discovers his neighbor is a beekeeper. But avoiding widow Ali Harding proves difficult when her eight-year-old son bonds with him and his dog. As Heath spends more time with them, his fear of bees--and heartbreak--could stand in the way of his happily-ever-after..."--Page 4 of cover.